Analysis of the effect of industrial transformation of resource-based cities in Northeast China - Gaolan Hou; Zhou Zou; Tianran Zhang; Yue Meng (Economies, 2019)
Based on the development of the industrial structure of prefecture-level resource-based cities in Northeast China, this paper selects three indicators of industrial structure-diversification, rationalization and upgrading-conducting empirical analysis on the transformation of the industrial structure of these resource-based cities. The effects of the industrial transformation of resource-based cities of the same kind are analysed and the development of industrial structure in different provinces is compared. It indicates that the transformation process and adjustment effect of the industrial structures in resource-based cities of Northeast China were different and were not very satisfactory on the whole and the secondary industry was still the leading industry in most cities. In addition, the article analyses the impact of the industrial transformation on the economic growth of resource-based cities in Northeast China. It can be concluded that the rationalization and upgrading of industrial structure generally promoted the cities' economic growth. The promotion of industrial structure rationalization was greater than that of upgrading. In order to promote the sustainable development of resource-based cities' economy in Northeast China and solve problems in the process of the cities' development, two suggestions are proposed. One is to pay attention to the rational development of the industrial structure, so it is necessary to strengthen the overall planning of resource-based cities in the Northeast region, promote regional coordination and rationally arrange and adjust the industrial structure from the overall scope of the region. Another is to continue to promote the process of industrial structure upgrading by introducing high-tech industries through preferential policies and to develop relevant industries based on the advantages of the cities, instead of just extending the original industry.
Keywords: O18; Q32; R11; 330; Northeast China; resource-based cities; industrial transformation